2022
DOI: 10.1017/s0033291721005092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the interactive effects of dietary habits and human gut microbiome on the risks of depression and anxiety

Abstract: Background Gut microbiome and dietary patterns have been suggested to be associated with depression/anxiety. However, limited effort has been made to explore the effects of possible interactions between diet and microbiome on the risks of depression and anxiety. Methods Using the latest genome-wide association studies findings in gut microbiome and dietary habits, polygenic risk scores (PRSs) analysis of gut microbiome and dietary habits was conducted in the UK Biobank cohort. Logistic/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…The software PRSice-2 is designed to calculate the PRS of an individual by aggregating and quantifying the effect of many single nucleotide polymorphisms (SNPs) in their genome, which are weighted by the effect sizes of each SNP derived from genome-wide association studies (GWASs) 19 . This approach has previously been used to explore the genetic relationship between gut microbial abundance and complex traits like bone mineral density, rheumatoid arthritis, and depression 20 22 . In the present study, we used this approach to determine the genetic relationship between 119 microbial genera and AD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The software PRSice-2 is designed to calculate the PRS of an individual by aggregating and quantifying the effect of many single nucleotide polymorphisms (SNPs) in their genome, which are weighted by the effect sizes of each SNP derived from genome-wide association studies (GWASs) 19 . This approach has previously been used to explore the genetic relationship between gut microbial abundance and complex traits like bone mineral density, rheumatoid arthritis, and depression 20 22 . In the present study, we used this approach to determine the genetic relationship between 119 microbial genera and AD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9–12 ] These findings suggested that the gut microbiota is a potential new target for stress‐induced depression and anxiety, and dietary interventions seem to be an easily accessible choice to relieve the mental disorders induced by chronic stress. [ 13–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Polygenic risk scores (PRSs) provide an overall estimate of the genetic predisposition for a trait at the individual level by calculating the sum of the effects of risk alleles, where each risk allele estimates the phenotype from an independent GWAS ( 21 ). Previously, PRS has also been used to assess the impact of d dietary habits and the gut microbiome on anxiety and depression ( 22 ).…”
Section: Introductionmentioning
confidence: 99%